Research and Practice on the Reform of Talent Training Mode of ‘Excellence Program’ in Water Conservancy Project - Huang, Hu; Zhao, Jiwei; Guo, Lixia; Xu, Xinyong (Journal of Educational Research and Policies, 2026)
In view of the current structural imbalance between supply and demand of talents in water conservancy projects and the insufficient reserve of national strategic talents, measures such as innovating talent training mode, optimizing medium mechanism and training scheme, creating school-enterprise joint practice and formulating training quality assurance system are taken. After years of practice, the teaching and research ability of high-level talents teachers has achieved remarkable results, the curriculum construction and teaching effect have been significantly improved, the students’ innovative spirit and comprehensive ability have been significantly improved, and the professional construction has achieved remarkable results. The results can provide reference for the construction of similar water conservancy projects.